Changes in Drinking Patterns, and Attitudes Toward and Knowledge About Alcohol Consumption During Pregnancy in a Population of Pregnant Danish Women. (6th May 2019) - Kesmodel, Ulrik Schiøler; Urbute, Aivara
Abstract : Background: In 1997, The Danish Health Authority recommended that "it is safest not to drink alcohol when you are pregnant, " and in 1999 expanded recommendations. There are only a few studies evaluating the possible change of average alcohol consumption following changes in national recommendations, and no studies have been found comparing the changes in pregnant women's attitudes toward alcohol consumption during pregnancy. We aimed to evaluate the changes in drinking pattern, and knowledge about and attitudes toward alcohol consumption during pregnancy before and after the change of national recommendations. Methods: This is a cross‐sectional interview study with a representative sample of 1, 418 woman attending antenatal care at the beginning of their second trimester in Aarhus, Denmark, in the year 2000, and a comparable sample of 439 pregnant women from 1998 in Aarhus. Participants were interviewed about their average alcohol consumption, binge drinking, and attitudes toward and knowledge about alcohol consumption during pregnancy. Data collection procedures and questions were identical for both samples. Results: There were no differences between the 2 samples in terms of average alcohol consumption before ( p = 0.19) and during ( p = 0.45) pregnancy, and binge drinking in early pregnancy ( p = 0.47). Attitudes toward and knowledge about alcohol in pregnancy did not change either ( p > 0.5). Women's knowledge about guidelines was less precise in 2000 ( p < 0.001). Worse knowledge was associated with younger age considering both samples (OR = 2.63, 95% CI: 1.63 to 4.26). Most pregnant women reported that they had not been informed or advised about alcohol consumption during pregnancy, but they would like to be advised by their healthcare professionals. Conclusions: After the changes in the national guidelines about alcohol consumption during pregnancy, there were no changes in behavior, attitudes, and knowledge of pregnant women. This would indicate that healthcare specialists should be encouraged to initiate a conversation about alcohol consumption during the first antenatal visit. Abstract : In 1999, Danish Health Authorities expanded recommendations of abstention to "drink no more than 1 drink/d; do not drink every day." We interviewed 439 pregnant women in 1998 and 1, 418 in 2000. After the changes in recommendations there were no changes in behavior, attitudes and knowledge of pregnant women, who reported that they had not been advised about alcohol consumption. This indicates that health care specialists should be encouraged to initiate conversation about alcohol consumption during the first antenatal visit.